GEOCHEMISTRY OF NATURAL AND CONTAMINATED SUBSURFACE WATERS IN FISSURED BED ROCKS OF THE LAKE KARACHAI AREA, SOUTHERN URALS, RUSSIA - Solodov I.N.; Zotov A.V.; Khoteev A.D.; Mukhamet-Galeev A.P.; Tagirov B.R.; Apps J.A. (My University, 1998)
Hydrogeochemical investigations of natural and contaminated subsurface waters were conducted between 1992–94 in an area where liquid radioactive waste (RAW) was impounded in a small lake, and subsequently leaked into an underlying water bearing horizon. The waste was discharged from the radiochemical plant of the Mayak Amalgamated Industry near Chelyabinsk, Russia. The underlying water-bearing horizon in fissured metavolcanic rocks was penetrated by uncased observation wells in order to log the hydrogeochemistry. Logging was carried out using a specially designed hydrogeochemical probe, which contained 8 channels to measure continuously the temperature, pressure, electric conductivity, pH, Eh, the dissolved O2 concentration, and the activities of Na, and NO3 in the wells. The logging technique enabled the natural hydrogeochemical setting to be characterized and permitted delineation of bodies of contaminated waters of different origins using measurements of pH, pNa and pNO3. The technique also permitted an evaluation of variations in the chemical composition of the RAW solutions due to radiolytic processes and to chemical interactions with the geologic medium. A conceptual model is proposed for the chemical evolution of the migrating contaminated subsurface waters in the area investigated.